1995
DOI: 10.1002/dvg.1020160107
|View full text |Cite
|
Sign up to set email alerts
|

Is the sphere organelle/coiled body a universal nuclear component?

Abstract: We present evidence for the essential homology of four nuclear organelles that have previously been described under four different names: coiled bodies in mammalian somatic nuclei, prenucleolar bodies in nuclei assembled in vitro in Xenopus egg extract, sphere organelles in amphibian germinal vesicles (GVs), and Binnenkörper in insect GVs. Each of these organelles contains coilin or a coilin-related protein plus a variety of small nuclear ribonucleoproteins. We suggest that the sphere organelle/coiled body is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
126
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 63 publications
3
126
0
Order By: Relevance
“…Earlier studies showed that coilin occurs exclusively in the matrix of oocyte CBs (Tuma et al, 1993;Wu et al, 1994), where it is colocalized with U7 snRNA (Wu and Gall, 1993). Splicing snRNAs, on the other hand, are limited to the B-snurposomes on the surface of CBs and to the internal B-like inclusions (Wu et al, 1991;Gall et al, 1995). Furthermore, by disrupting U7 snRNA with an antisense oligodeoxynucleotide, we showed that U7 is the major capped snRNA associated with coilin in oocyte CBs.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Earlier studies showed that coilin occurs exclusively in the matrix of oocyte CBs (Tuma et al, 1993;Wu et al, 1994), where it is colocalized with U7 snRNA (Wu and Gall, 1993). Splicing snRNAs, on the other hand, are limited to the B-snurposomes on the surface of CBs and to the internal B-like inclusions (Wu et al, 1991;Gall et al, 1995). Furthermore, by disrupting U7 snRNA with an antisense oligodeoxynucleotide, we showed that U7 is the major capped snRNA associated with coilin in oocyte CBs.…”
mentioning
confidence: 54%
“…They are characterized by the presence of a unique protein, p80-coilin , along with components involved in three different RNA-processing pathways: splicing, prerRNA processing, and histone pre-mRNA processing (reviewed by Lamond and Carmo-Fonseca, 1993;Bohmann et al, 1995;Gall et al, 1995;Roth, 1995;Lamond and Earnshaw, 1998;Matera, 1998). Long before their homology to somatic CBs was recognized, CBs had been described from the oocyte nucleus or germinal vesicle (GV) of insects (Jö rgensen, 1913) and amphibians (Gall, 1954;Callan and Lloyd, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…It could provide a mechanism for the import of factors involved in nucleolar transcript processing, such as fibrillarin, into the nucleolus, or it might provide a mechanism for shuttling of proteins such as Nopp140 and NAP57 between the nucleoplasm and nucleolus. Alternatively, the coiled body might be the initial site for assembly of processing complexes, which are then sorted to other locations in the nucleus or nucleolus where the actual RNP processing takes place, as suggested earlier by Gall et al (1995).…”
Section: Discussionmentioning
confidence: 94%
“…Because coiled bodies do not contain DNA, nascent pre-mRNA, heterogeneous nuclear RNPs (hnRNPs), or the SC-35 splicing factor, which is required for splicing in vitro, it has been argued that they are not directly involved in transcription and pre-mRNA splicing . However, it has been speculated that coiled bodies may be sites of splicing factor assembly or recycling, may play a role in histone mRNA 3Ј processing (Gall et al, 1995;Lamond and Earnshaw, 1998), or may be involved in all these activities. As coiled bodies are frequently observed at the nucleolar periphery and also in the nucleoplasm and within nucleoli (Malatesta et al 1994;Ochs et al, 1994), they may also act as nuclear transport or sorting structures.…”
Section: Introductionmentioning
confidence: 99%
“…Coilin is highly conserved among vertebrates and clear homologs can be found in plants (Tucker and Matera 2004), but the gene has not been identified in worms and flies. Although coilin appears to be absent from the genomes of worms and flies, structures similar to CBs have been identified in various insects including Drosophila (Gall et al 1995;Jady et al 2003;Yannoni and White 1997). Moreover, coilin is required for the accumulation of U snRNPs within the CBs of amphibians and mammals (Bauer and Gall 1997;Hebert et al 2001;Tucker et al 2001).…”
Section: Introductionmentioning
confidence: 99%